Epistemic Communities, Between Science and Power in International Domains: A Systematic Literature Review - Pratiwi (UIN ALAUDDIN MAKASSAR, 2024)
Epistemic communities were emphasized in constructivism discourse as powerful emerging non-state actors that can drive policies in international domains. The rise of scientific consortiums in policymaking has driven policy directions by using scientific standards. Other realms in international relations also recognize the roles of scientific communities other than creating standards to fix global challenges, such as to serve states’ interests and cooperation tools. This study aims to investigate which realm of epistemic communities are more prevalent. The tools and conditions for influential epistemic communities were also not sufficiently investigated. By using a systematic literature review (SLR) that is overlooked in international relations studies, this paper organized previous databases that use primary data on epistemic communities. The result of this paper shows epistemic communities are the most prevalent in creating scientific standards to address global challenges. Some tools that used were knowledge transfers, training, research collaborations, and networking funding. However, other studies also found that scientific consortiums may be used to legitimize the status quo. In sensitive issues like transboundary pollution, more distrust was found. This study eventually draws some limitations and agenda for future studies.